Epidermal aquaporin-3 is increased in the cutaneous burn wound. Issue 4 (June 2015) - Sebastian, R.; Chau, E.; Fillmore, P.; Matthews, J.; Price, L.A.; Sidhaye, V.; Milner, S.M.
Highlights In the skin, AQPs permit rapid, regulated, and selective water permeability and have been demonstrated to play a role in skin hydration, cell proliferation, migration, immunity, and wound healing. The burn wound edge demonstrates a partial loss of the epidermal architecture representing a partial thickness burn. In the burn wound center there is a complete loss of the epidermis and dermis representing a full thickness burn. Aquaporin-3 expression is absent in the burn wound center. There is a significant increase in the quantity of aquaporin-3 expression along the burn wound edge compared to the burn wound center.